Naẓariyāt fī Takāmul al-‘Ulūm: Dirāsah Naqdīyah wa Ta’sīsīyah fī Thaqāfat al-Minangkabau - Eka Putra Wirman (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2016)
This article aims at identifying various concepts of science at Islamic Universities in Indonesia, especially after the conversion of a number of State Islamic Institute (IAIN) into the State Islamic University (UIN). After analyzing the existing concepts and its shortcomings, this study offers a new pespective that is derived from Minangkabau local wisdom as an alternative. The study uses text analysis methods against various science concepts adopted by various state Islamic universities, such as “Web Spiders”; “Tree of Science”, and “Integration of Science” Through a comparative study between various opinions and work around the Minangkabau tradition, it was concluded that the current concepts being applied are mostly based on the dichotomy of science, where a discipline only applies in a particular period, and does not apply at other times. This sort of dichotomy in turn leads to a vacuum and underdevelopment, even shutting down the growth and progress of certain sciences. Therefore, this study offers a new scientific paradigm called “Tali Tigo Sapilin” which is based on local wisdom of Minangkabau culture with its characteristics, such as balance, synergy and collaboration.DOI: 10.15408/sdi.v23i1.2105